Produção e caracterização de iogurte simbiótico sabor banana, obtido a partir de leite de vaca e de cabra, cultura probiótica e polpa de banana verde - Lucatto, Juliana Nunes (2013)
The growing demand from consumers for foods that beyond basic nutritional functions, exert beneficial health effects has stimulated researchers and the food industry to develop functional dairy products. In this class, special attention has been given to the development of yoghurt with probiotic and prebiotic properties, called symbiotic. Numerous mechanisms have been proposed to explain the benefits of consuming dairy symbiotic products, including the ability of probiotic microorganisms on conjugated linoleic acid production. The use of this compound has been associated with beneficial health effects, such as anticarcinogenic properties, modulation of the immune system, reduction of atherosclerosis, among others. The overall aim of this study was the production and characterization of a symbiotic banana flavored yogurt obtained from cow and goat milk, probiotic cultures Lactobacillus acidophilus and Bifidobacterium animalis subsp lactis Bb-12 and green banana pulp as resistant starch source. To achieve this goal, the following steps were carried out: literature review about conjugated linoleic acid, analysis of the chemical composition and physicochemical properties of cow's milk, goat milk, green banana, green banana pulp and yoghurt produced; checking the viability of the probiotic microorganism Lactobacillus acidophilus and Bifidobacterium animalis subsp lactis Bb-12 by enumeration during the useful life of the products (time 0, 15, 30 and 45 days); quantification of the microorganisms Lactobacillus delbruecki subsp. bulgaricus and Streptococcus salivarius subps. thermophilus as starter culture employed in the preparation of yoghurt during the product lifetime (time 0, 15, 30 and 45 days); profile study of texture (hardness, cohesiveness, elasticity or gumminess) and apparent viscosity of different treatments during yogurt lifetime (0, 15, 30 and 45 days) and determining color (parameter L * and a * b * coordinates) of different formulations of yogurts during the lifetime (0, 15, 30 and 45 days), market study and finally, the sensory analysis of yoghurt prepared. The six yogurt formulations achieved the legal requirements for the physico-chemical properties, for the centesimal composition and for microbiological enumeration. Still, significant differences were observed in the centesimal composition, the physico-chemical properties, color and texture profiles and sensory analysis of yogurt made with cow’s milk from those made with goat’s milk.